Assessment of land use changes in the Verde River basin using two hydrological models. (October 2022) - Carvalho, Vinícius S.O.; da Cunha, Zandra A.; Alvarenga, Lívia A.; Beskow, Samuel; de Mello, Carlos R.; Martins, Minella A.; de M.M. de Oliveira, Conceição
Abstract: Land use changes can affect hydrological cycle dynamics, mainly groundwater recharge and infiltration-runoff relationships. The objective of this study was to evaluate the application of the Variable Infiltration Capacity (VIC) and Lavras Simulation of Hydrology (LASH) hydrological models and analyse the impacts of land use changes on the hydrological regime in the Verde River basin of southeastern Brazil. The land use change scenarios were developed considering demographic, agricultural and economic indicators as follows: 20% (S1) and 50% (S2) conversion of pasture into eucalyptus; 20% (S3) and 50% (S4) conversion of native forest into pasture; and 20% conversion of pasture into forest (S5). The CNS (Nash-Sutcliffe) values varied from 0.77 to 0.88 for daily and monthly fit during calibration (1993–1999) and validation (2000–2005) periods. The LASH model showed a better capacity to reproduce the regular streamflow regime than the VIC model. The reforestation scenarios (S1, S2, and S5) showed a decrease in total runoff, mainly due to the increase in evapotranspiration and canopy interception, while the deforestation scenarios (S3 and S4) showed the opposite effects. Differences in the structure and representation of hydrological processes in hydrological models must be considered to predict the impacts of land use changes on the hydrology of tropical and subtropical basins. Highlights: Land use changes can affect hydrological cycle dynamics. Application of the Variable Infiltration Capacity (VIC) hydrological models. Application of the Lavras Simulation of Hydrology (LASH) hydrological models. Changes on the hydrological regime.